INSPIRING AND ENHANCING THE SUCCESS MOTIVATION OF JUNIOR HIGH SCHOOL STUDENTS AT SMP ISLAM BELIK - Irawan Randikaparsa; Akhmad Fauzan; Rifka Utami Arofah; Deska Salsabila (Midang, 2023)
Education is the main pillar in shaping the future of the younger generation. In the midst of a critical phase of development for junior high school children, motivation plays a central role in encouraging them to achieve success in education and personal development. In this context, this service journal, entitled “Inspiring and Enhancing the Success Motivation of Junior High School Students at SMP Islam Belik,” documents collaborative efforts aimed at increasing student learning motivation at Belik Islam Middle School. The service is carried out using presentations and also watching motivational films to encourage students to learn. The results of this activity show that Beluk Islamic Middle School students are motivated to continue their education and achieve their dreams..